Decrease of CD69 levels on TCR Vα7.2+CD4+ innate-like lymphocytes is associated with impaired cytotoxic functions in chronic hepatitis B virus-infected patients - Yong, Y.K.; Tan, H.Y.; Saeidi, A.; Mohamed, R.; Atiya, N.; Ansari, A.W.; Rajarajeswaran, J.; Vadivelu, J.; Velu, V.; Larsson, M.; Shankar, E.M. (SAGE Publications (UK and US), 2017)
Hepatitis B virus (HBV) infection is a major cause of chronic liver disease that may progress to liver cirrhosis and hepatocellular carcinoma. Host immune responses represent the key determinants of HBV clearance or persistence. Here, we investigated the role of the early activation marker, CD69 and effector cytokines, granzyme B (GrB) and IFN-γ in the exhaustion of innate-like TCR Vα7.2+CD4+T cells, in 15 individuals with chronic HBV (CHB) infection where six were HBV DNA+ and nine were HBV DNA-. The percentage of cytokine-producing T cells and MAIT cells were significantly perturbed in HBV patients relative to healthy controls (HCs). The intracellular expression of GrB and IFN-γ was significantly reduced in MAIT cells derived from HBV-infected patients as compared to HCs, and the levels correlated with the percentage and levels [mean fluorescence intensity (MFI)] of CD69 expression. The total expression of CD69 (iMFI) was lower in CHB patients as compared to HCs. The frequency of CD69+ cells correlated with the levels of cytokine expression (MFI), particularly in CHB patients as compared to HCs. In summary, the polyfunctionality of peripheral T cells was significantly reduced among CHB patients, especially in the TCR Vα7.2+CD4+T cells, and the levels of cytokine expression correlated with functional cytokine levels.